2005
DOI: 10.1177/0115426505020004377
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Review of Nutrition Considerations in the Pediatric Oncology Population: A Perspective From Children's Oncology Group

Abstract: Over the past few decades, great progress has been made in the survival rates of childhood cancer. As survival rates have improved, there has been an increased focus on supportive care. Nutrition is a supportive-care modality that has been associated with improved tolerance to chemotherapy, improved survival, increased quality of life, and decreased risk of infection in children undergoing anticancer therapy. Guidelines and assessment criteria have been proposed for the nutrition management of a child with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
162
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 133 publications
(136 reference statements)
3
162
0
4
Order By: Relevance
“…20 It has been established that underweight children with leukemia and solid tumors have an increased rate of relapse and worse survival. 3,4,21 A significant difference in survival was not observed between the underweight and ideal-weight groups. Although not significant, an increased HR was observed with large confidence intervals, indicating that further investigation with larger numbers in the underweight group is required.…”
Section: Discussionmentioning
confidence: 87%
“…20 It has been established that underweight children with leukemia and solid tumors have an increased rate of relapse and worse survival. 3,4,21 A significant difference in survival was not observed between the underweight and ideal-weight groups. Although not significant, an increased HR was observed with large confidence intervals, indicating that further investigation with larger numbers in the underweight group is required.…”
Section: Discussionmentioning
confidence: 87%
“…Table 1 reveals A total of 30 children with newly diagnosed ALL were included in this study, their age range from (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years, mean age (5.4 ± 3.4SD). Sixteen were males and fourteen were females, reveals that 16 (53.3%) of patients included in this study were males and 14 (46.6%) were females.…”
Section: Discussionmentioning
confidence: 99%
“…This has been linked to the escalation of obesity in pediatric ALL survivors, which is four to five times more likely than expected, Leukemia and lymphoma patients can have an enlarged spleen, this effect on the patient's stomach thus reducing their appetite [5]. Nutrition is a supportive care modality that has associated with improved tolerance to chemotherapy, improved survival, increased quality of life, and decreased risk of infection in children undergoing anticancer therapy [6]. The goal of nutritional assessment in childhood is to prevent nutritional disorders and the increased morbidity and mortality that accompany them.…”
Section: Introductionmentioning
confidence: 99%
“…It comprises an increased infection rate, which contributes to a poor outcome of the disease. 13,17 A meta-analysis to assess the effects of zinc supplementation on physical growth of children revealed a highly positive response in weight and height increments. 18 This study showed that 28.9% of the patients needed a nutritional intervention at the moment of the first evaluation, bearing in mind the malnourished status and the consumptive characteristic of leukemia.…”
Section: Discussionmentioning
confidence: 99%